Aerobic Exercise Improves Mood, Cognition, and Language Function in Parkinson's Disease: Results of a Controlled Study. (22nd September 2016) - Altmann, Lori J.P.; Stegemöller, Elizabeth; Hazamy, Audrey A.; Wilson, Jonathan P.; Bowers, Dawn; Okun, Michael S.; Hass, Chris J.
Abstract: Objectives: Parkinson's disease (PD) results in a range of non-motor deficits that can affect mood, cognition, and language, and many of these issues are unresponsive to pharmacological intervention. Aerobic exercise can improve mood and cognition in healthy older adults, although only a few studies have examined exercise effects on these domains in PD. The current study assesses the effects of aerobic exercise on aspects of cognition, mood, and language production in people with PD.Methods: This study compares the effects of aerobic exercise to stretch-balance training and a no-contact control group in participants with idiopathic PD. The aerobic and stretch-balance groups trained three times a week for 16 weeks, while controls continued normal activities. Outcome measures included disease severity, mood, cognition (speed of processing, memory, and executive function), and language production (picture descriptions). Cognition and language were assessed in single and dual task conditions.Results: Depressive symptoms increased only in the control group ( p <.02). Executive function improved in the aerobic exercise group only in the single task ( p =.007) and declined in controls in the dual task. Completeness of picture descriptions improved significantly more in the aerobic group than in the stretch-balance group ( p <.02).Conclusions: Aerobic exercise is a viable intervention for PD that can be protective against increased depressive symptoms, and can improve several non-motor domains, including executive dysfunction and related aspects of language production. ( JINS, 2016, 22, 878–889)